Method for improving structural stability and exchange bias effect of SrFeO3-delta perovskite oxide

By incorporating Y and Ni ions into SrFeO3-δ, Sr0.9Y0.1Fe1-xNixO3-δ polycrystalline blocks were prepared, which solved the problems of perovskite structural oxide structural stability and exchange bias field, achieved improvements in structural stability and exchange bias effect, simplified the preparation process and reduced costs.

CN119683987APending Publication Date: 2025-03-25KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510054029.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, there are some unsolved problems in the structural stability and exchange bias field of perovskite structural oxides, which affect their application in device performance and scientific research.

Method used

By adding rare earth element Y ions to the A position of SrFeO3-δ and adding Ni ions to the B position gradient, SrFeO3-δ polycrystalline blocks containing Sr0.9Y0.1Fe1-xNixO3-δ were prepared to modulate their structural stability and exchange bias effect.

Benefits of technology

It effectively improves the structural stability and exchange bias effect of SrFeO3-δ polycrystalline blocks, simplifies the preparation process, reduces production costs, and provides valuable suggestions for improving the difficulty in forming perovskite structures and the development of magnetic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683987A_ABST
    Figure CN119683987A_ABST
Patent Text Reader

Abstract

The invention relates to the field of functional material preparation, in particular to a method for improving the structural stability and the exchange bias effect of SrFeO3-delta perovskite oxide. The method comprises the following steps: performing pressing and high-temperature treatment on raw material mixed powder, doping rare earth element Y ions into the A site of SrFeO3-delta, and doping Ni ions into the B site of SrFeO3-delta in a gradient manner to obtain a SrFeO3-delta polycrystalline bulk containing Sr0. 9Y0. 1Fe1-xNixO3-delta so as to modulate the structural stability and exchange bias effect of the SrFeO3-delta polycrystalline bulk, wherein x is equal to 0 to 0.3. The preparation process is simple, the production cost is low, and valuable suggestions are provided for improving the difficulty in forming the SrFeO3-delta perovskite structure and developing magnetic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of functional materials, in particular to improving SrFeO 3-δ Methods for structural stability and exchange bias effects in perovskite oxides. Background Art

[0002] Perovskite structured oxides have been favored by researchers due to their unique physical properties and broad application prospects. The standard perovskite oxide has an ABO3 structure. The A-site ions represent alkaline earth or rare earth ions with larger ionic radius. Generally, the A-site ions will form the closest cubic stacking with 12 oxygen ions to obtain a stable perovskite structure. The B-site ions are generally metal elements with smaller ionic radius and occupy the center of the octahedron. The BO6 octahedron can expand, shrink and tilt according to the size of the ions to achieve structural stability. In addition, in the case of an unstable electronic structure, the octahedron can also be distorted, or the cations may deviate from their ideal position. Due to this flexibility, the perovskite structure can accommodate almost all elements in the periodic table in various forms. SrFeO 3-δ Materials are one of them, with many specific and good physical and chemical properties. The exchange bias effect refers to the fact that when a ferromagnetic (FM) / antiferromagnetic (AFM) system is cooled from a temperature higher than the antiferromagnetic Neel temperature but lower than the Curie temperature of the ferromagnetic layer to a temperature below the antiferromagnetic Neel temperature (i.e., after a field cooling process) in an external magnetic field, the hysteresis loop of the ferromagnetic layer will deviate from the origin along the direction of the magnetic field, and the amount of deviation is called the exchange bias field, accompanied by an increase in coercive force. The exchange bias field of the ferromagnetic / antiferromagnetic system has rich physical significance and important application value in giant magnetoresistance devices, so it has attracted much attention.

[0003] Although there have been relevant basic research and applications on the structural stability and exchange bias field of perovskite structured oxides in the existing technology, there are still some issues that are not very clear and are also hot topics for people to study. 3-δ Perovskite oxides are of great significance in terms of application areas, improving device performance, and promoting the development of related scientific research. Summary of the invention

[0004] In view of the problems existing in the background technology, it is proposed to improve SrFeO 3-δ The present invention has a simple preparation process and low production cost, and is suitable for improving the structural stability and exchange bias effect of SrFeO 3-δ The perovskite structure is difficult to shape and provides valuable suggestions for the development of magnetic devices.

[0005] The present invention proposes to increase SrFeO 3-δThe method of structural stability and exchange bias effect of perovskite oxides is to press and treat the raw material mixed powder at high temperature to obtain SrFeO 3-δ The rare earth element Y ion is doped into the A position of SrFeO 3-δ The B-site of the Sr-containing 0.9 Y 0.1 Fe 1-x Ni x O 3-δ SrFeO 3-δ Polycrystalline bulk material, to modulate SrFeO 3-δ Structural stability and exchange bias effect of polycrystalline bulk materials; where x = 0-0.3.

[0006] Preferably, the specific steps are as follows:

[0007] S1. Weigh, mix, grind and press SrCO3, Fe2O3, Y2O3 and NiO powders in molar ratio into blocks;

[0008] S2, placing the block obtained in S1 in a crucible for high temperature solid phase sintering, and obtaining SrFeO after furnace cooling. 3-δ和 Sr 0.9 Y 0.1 Fe 1-x Ni x O 3-δ of polycrystalline bulk material.

[0009] Preferably, the molar ratio of Sr:Fe elements is 1:0.5; the molar ratio of Sr:Y:Fe:Ni elements is 0.9:0.05:(1-x) / 2:x; x=0-0.3.

[0010] Preferably, the purity of the raw material in S1 is ≥99%.

[0011] Preferably, the grinding time of the mixed raw materials in S1 is 1.5-2.5 hours, the first tableting process is uniaxial pressure 3-4MPa, the second is 7-8MPa, the two holding times are 5 minutes, and the block size is a columnar body of Ф20×3mm.

[0012] Preferably, the specific process of the two high-temperature solid-phase sinterings in S2 is: the first sintering is heated from room temperature to 950°C and kept for 2h, then heated to 1180°C and kept for 24h, then cooled to 600°C and kept for 30min, then cooled to room temperature with the furnace, and then sintered for the second time; the secondary sintering process is the same as the first sintering, with a heating rate of 5°C / min, a cooling rate of 5°C / min, and the sintering atmosphere is air.

[0013] Preferably, a superconducting quantum interference device is used to measure the hysteresis loop of the polycrystalline bulk material obtained by S2.

[0014] Preferably, the block is ground into powder for measurement.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: the present invention processes the raw material mixed powder by pressing and high temperature treatment, and obtains SrFeO 3-δ The rare earth element Y ion is doped into the A position of SrFeO 3-δ The B-site of the Sr-containing 0.9 Y 0.1 Fe 1-x Ni x O 3-δ SrFeO 3-δ Polycrystalline bulk materials effectively improve their structural stability and exchange bias effect. They are prepared by a simple solid-phase reaction method, which is simple and low-cost, and provides valuable suggestions for improving the difficulty of forming perovskite structures and the development of magnetic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The XRD pattern of the sample obtained in Example 1 and the optical photographs before and after standing are shown.

[0017] Figure 2 is Sr in Embodiment 1 to Embodiment 5 0.9 Y 0.1 Fe 1-x Ni x O 3-δ (x=0-0.3) Schematic diagram of the hysteresis loop of polycrystalline bulk material. DETAILED DESCRIPTION

[0018] Embodiment 1

[0019] The invention proposes to improve SrFeO 3-δ The method for structural stability and exchange bias effect of perovskite oxide specifically comprises the following steps:

[0020] 1. SrCO3, Fe2O3, Y2O3, and NiO powders were weighed, mixed, and ground for 2 h (x = 0) at a molar ratio of Sr:Fe = 1:0.5, Sr:Y:Fe:Ni = 0.9:0.05: (1-x) / 2:x, respectively, and then the mixed raw materials were pressed into a columnar raw material block with a diameter of 20 mm and a thickness of about 3 mm under a uniaxial pressure of 3-4 MPa and a holding time of 5 minutes;

[0021] 2. Place the raw material block obtained in step 1 in a corundum crucible for high-temperature sintering. After furnace cooling, grind and press the sheet again (uniaxial pressure 7-8MPa) for secondary sintering. Finally, after furnace cooling, SrFeO 3-δ , Sr 0.9 Y 0.1 Fe 1-x Nix O 3-δ (x=0) polycrystalline bulk.

[0022] The high temperature sintering process is 1180℃ / 24h+1180℃ / 24h secondary sintering; the specific process is to increase the temperature from room temperature to 950℃, keep it for 2h, then increase it to 1180℃, sinter it for 24h, then reduce it to 600℃ and keep it for 30min, and then cool it with the furnace; the secondary sintering process is the same as the primary sintering process. After it is reduced to room temperature, the secondary sintering of the same process is carried out; the heating rate is 5℃ / min, the cooling rate is 5℃ / min, and the sintering atmosphere is air.

[0023] 3. Measuring Sr using a superconducting quantum interference device (SQUID) 0.9 Y 0.1 Fe 1-x Ni x O 3-δ (x=0) Magnetic hysteresis loop of polycrystalline bulk material.

[0024] Embodiment 2

[0025] The invention proposes to improve SrFeO 3-δ The method for structural stability and exchange bias effect of perovskite oxide specifically comprises the following steps:

[0026] 1. SrCO3, Fe2O3, Y2O3, and NiO powders were weighed, mixed, and ground for 2 h (x = 0.05) at a molar ratio of Sr:Fe = 1:0.5, Sr:Y:Fe:Ni = 0.9:0.05: (1-x) / 2:x, respectively, and then the mixed raw materials were pressed into a columnar raw material block with a diameter of 20 mm and a thickness of about 3 mm under a uniaxial pressure of 3-4 MPa and a holding time of 5 minutes;

[0027] 2. Place the raw material block obtained in step 1 in a corundum crucible for high-temperature sintering. After furnace cooling, grind and press the sheet again (uniaxial pressure 7-8MPa) for secondary sintering. Finally, after furnace cooling, SrFeO 3-δ , Sr 0.9 Y 0.1 Fe 1-x Ni x O 3-δ (x=0.05) polycrystalline bulk.

[0028] The high temperature sintering process is 1180℃ / 24h+1180℃ / 24h secondary sintering; the specific process is to increase the temperature from room temperature to 950℃, keep it for 2h, then increase it to 1180℃, sinter it for 24h, then reduce it to 600℃ and keep it for 30min, and then cool it with the furnace; the secondary sintering process is the same as the primary sintering process. After it is reduced to room temperature, the secondary sintering of the same process is carried out; the heating rate is 5℃ / min, the cooling rate is 5℃ / min, and the sintering atmosphere is air.

[0029] 3. Measuring Sr using a superconducting quantum interference device (SQUID) 0.9 Y 0.1 Fe 1-x Ni x O 3-δ (x=0.05) Magnetic hysteresis loop of polycrystalline bulk material.

[0030] Embodiment 3

[0031] The invention proposes to improve SrFeO 3-δ The method for structural stability and exchange bias effect of perovskite oxide specifically comprises the following steps:

[0032] 1. SrCO3, Fe2O3, Y2O3, and NiO powders were weighed, mixed, and ground for 2 h (x = 0.1) at a molar ratio of Sr:Fe = 1:0.5, Sr:Y:Fe:Ni = 0.9:0.05: (1-x) / 2:x, respectively, and then the mixed raw materials were pressed into a columnar raw material block with a diameter of 20 mm and a thickness of about 3 mm under a uniaxial pressure of 3-4 MPa and a holding time of 5 minutes;

[0033] 2. Place the raw material block obtained in step 1 in a corundum crucible for high-temperature sintering. After furnace cooling, grind and press the sheet again (uniaxial pressure 7-8MPa) for secondary sintering. Finally, after furnace cooling, SrFeO 3-δ , Sr 0.9 Y 0.1 Fe 1-x Ni x O 3-δ (x=0.1) polycrystalline bulk.

[0034] The high temperature sintering process is 1180℃ / 24h+1180℃ / 24h secondary sintering; the specific process is to increase the temperature from room temperature to 950℃, keep it for 2h, then increase it to 1180℃, sinter it for 24h, then reduce it to 600℃ and keep it for 30min, and then cool it with the furnace; the secondary sintering process is the same as the primary sintering process. After it is reduced to room temperature, the secondary sintering of the same process is carried out; the heating rate is 5℃ / min, the cooling rate is 5℃ / min, and the sintering atmosphere is air.

[0035] 3. Measuring Sr using a superconducting quantum interference device (SQUID)0.9 Y 0.1 Fe 1-x Ni x O 3-δ (x=0.1) Magnetic hysteresis loop of polycrystalline bulk material.

[0036] Embodiment 4

[0037] The invention proposes to improve SrFeO 3-δ The method for structural stability and exchange bias effect of perovskite oxide specifically comprises the following steps:

[0038] 1. SrCO3, Fe2O3, Y2O3, and NiO powders were weighed, mixed, and ground for 2 h (x = 0.2) at a molar ratio of Sr:Fe = 1:0.5, Sr:Y:Fe:Ni = 0.9:0.05: (1-x) / 2:x, respectively, and then the mixed raw materials were pressed into a columnar raw material block with a diameter of 20 mm and a thickness of about 3 mm under a uniaxial pressure of 3-4 MPa and a holding time of 5 minutes;

[0039] 2. Place the raw material block obtained in step 1 in a corundum crucible for high-temperature sintering. After furnace cooling, grind and press the sheet again (uniaxial pressure 7-8MPa) for secondary sintering. Finally, after furnace cooling, SrFeO 3-δ , Sr 0.9 Y 0.1 Fe 1-x Ni x O 3-δ (x=0.2) polycrystalline bulk.

[0040] The high temperature sintering process is 1180℃ / 24h+1180℃ / 24h secondary sintering; the specific process is to increase the temperature from room temperature to 950℃, keep it for 2h, then increase it to 1180℃, sinter it for 24h, then reduce it to 600℃ and keep it for 30min, and then cool it with the furnace; the secondary sintering process is the same as the primary sintering process. After it is reduced to room temperature, the secondary sintering of the same process is carried out; the heating rate is 5℃ / min, the cooling rate is 5℃ / min, and the sintering atmosphere is air.

[0041] 3. Measuring Sr using a superconducting quantum interference device (SQUID) 0.9 Y 0.1 Fe 1-x Ni x O 3-δ (x=0.2) Magnetic hysteresis loop of polycrystalline bulk material.

[0042] Embodiment 5

[0043] The invention proposes to improve SrFeO 3-δ The method for structural stability and exchange bias effect of perovskite oxide specifically comprises the following steps:

[0044] 1. SrCO3, Fe2O3, Y2O3, and NiO powders were weighed, mixed, and ground for 2 h (x = 0.3) at a molar ratio of Sr:Fe = 1:0.5, Sr:Y:Fe:Ni = 0.9:0.05: (1-x) / 2:x, respectively, and then the mixed raw materials were pressed into a columnar raw material block with a diameter of 20 mm and a thickness of about 3 mm under a uniaxial pressure of 3-4 MPa and a holding time of 5 minutes;

[0045] 2. Place the raw material block obtained in step 1 in a corundum crucible for high-temperature sintering. After furnace cooling, grind and press the sheet again (uniaxial pressure 7-8MPa) for secondary sintering. Finally, after furnace cooling, SrFeO 3-δ , Sr 0.9 Y 0.1 Fe 1-x Ni x O 3-δ (x=0.3) polycrystalline bulk.

[0046] The high temperature sintering process is 1180℃ / 24h+1180℃ / 24h secondary sintering; the specific process is to increase the temperature from room temperature to 950℃, keep it for 2h, then increase it to 1180℃, sinter it for 24h, then reduce it to 600℃ and keep it for 30min, and then cool it with the furnace; the secondary sintering process is the same as the primary sintering process. After it is reduced to room temperature, the secondary sintering of the same process is carried out; the heating rate is 5℃ / min, the cooling rate is 5℃ / min, and the sintering atmosphere is air.

[0047] 3. Measuring Sr using a superconducting quantum interference device (SQUID) 0.9 Y 0.1 Fe 1-x Ni x O 3-δ (x=0.3) Magnetic hysteresis loop of polycrystalline bulk material.

[0048] like Figure 1 As shown, based on Example 1 SrFeO 3-δ After 12 hours of standing, the polycrystalline block showed visible cracks. 3-δ The Sr 0.9 Y 0.1 FeO 3-δ After standing for 12 hours, the polycrystalline block showed no cracks, the block structure remained good, and the original crystal structure was not changed. Figure 2 As shown, in Sr 0.9 Y 0.1 FeO 3-δ The Ni ions were introduced into the B-site gradient to prepare Sr 0.9 Y 0.1 Fe 1-x Nix O 3-δ (x=0-0.3) series of polycrystalline bulk materials show obvious exchange bias effect, among which Sr 0.9 Y 0.1 Fe 0.9 Ni 0.1 O 3-δ The offset is most obvious.

[0049] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited thereto, and various changes can be made within the knowledge scope of technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. Improve SrFeO 3-δ A method for structural stability and exchange bias effect of perovskite oxides, characterized in that, By pressing and high temperature treatment of raw material mixed powder, SrFeO 3-δ The rare earth element Y ion is doped into the A position of SrFeO 3-δ The B-site of the Sr-containing 0.9 Y 0.1 Fe 1-x Ni x O 3-δ SrFeO 3-δ Polycrystalline bulk material, to modulate SrFeO 3-δ Structural stability and exchange bias effects of polycrystalline bulk materials; Where x = 0-0.

3.

2. The method for improving SrFeO according to claim 1 3-δ A method for structural stability and exchange bias effect of perovskite oxides, characterized in that, Here are the steps: S1. Weigh, mix, grind and press SrCO3, Fe2O3, Y2O3 and NiO powders in molar ratio into blocks; S2, placing the block obtained in S1 in a crucible for high temperature solid phase sintering, and obtaining SrFeO after furnace cooling. 3-δ和 Sr 0.9 Y 0.1 Fe 1-x Ni x O 3-δ of polycrystalline bulk material.

3. The method for improving SrFeO according to claim 2 3-δ A method for structural stability and exchange bias effect of perovskite oxides, characterized in that, The molar ratio of Sr:Fe elements is 1:0.5; the molar ratio of Sr:Y:Fe:Ni elements is 0.9:0.05:(1-x) / 2:x; x=0-0.

3.

4. The method for improving SrFeO according to claim 2 3-δ A method for structural stability and exchange bias effect of perovskite oxides, characterized in that, The purity of the raw material described in S1 is ≥ 99%.

5. The method for increasing SrFeO according to claim 2 3-δ The method for the structural stability and exchange bias effect of perovskite oxides, the grinding time of the mixed raw materials in S1 is 1.5-2.5 hours, the first tableting process is a uniaxial pressure of 3-4MPa, the second is 7-8MPa, the two holding times are 5 minutes, and the block size is a columnar body of Ф20×3mm.

6. According to claim 2, the method for increasing SrFeO 3-δ A method for structural stability and exchange bias effect of perovskite oxides, characterized in that, The specific process of the two high-temperature solid-phase sinterings in S2 is as follows: the first sintering is from room temperature to 950℃ and kept for 2h, then raised to 1180℃ and kept for 24h, then cooled to 600℃ and kept for 30min, then cooled to room temperature with the furnace, and then sintered for the second time; the secondary sintering process is the same as the first sintering, with a heating rate of 5℃ / min, a cooling rate of 5℃ / min, and the sintering atmosphere is air.

7. According to claim 2, the method for increasing SrFeO 3-δ A method for structural stability and exchange bias effect of perovskite oxides, characterized in that, The hysteresis loop of polycrystalline bulk material S2 was measured using superconducting quantum interference device.

8. The method for increasing SrFeO according to claim 7 3-δ A method for structural stability and exchange bias effect of perovskite oxides, characterized in that, The block needs to be ground into powder for measurement.